Evaluación geométrica de la saturación, presión de dióxido de carbono y oxígeno de gases venosos (2016)
Background: The chaotic behavior of normal and acute cardiac dynamics has been evaluated correctly for 16 hours in the context of the theory of dynamical systems and fractal geometry. Objective: To establish a new mathematical and geometric measure to characterize venous oxygen saturation (SvO2), venous oxygen pressure (PvO2) and venous carbon dioxide pressure (PvCO2), in the context of dynamic systems theory. Material and methods: The values of the SvO2, the PvO2 and the PvCO2 were taken from the clinical reports of gases from 10 patients to build chaotic attractors on the delay map, then the minimum and maximum values of the entire attractor were calculated. Results: The minimum and maximum values of the attractors of venous oxygen saturation, oxygen venous pressure and carbon dioxide venous pressure varied between 49.30 and 99.80%, 26.10 and 96.40 mmHg, 27.60 and 57.80 mmHg, respectively. Conclusions: Chaotic behavior of the hemodynamic variables was observed, which was measured from the minimum and maximum values for each attractor thus establishing a new mathematical, geometrical and physical measurement to assess these three hemodynamic variables of interest in the Intensive Care Unit. © 2016 Asociacion Nacional de Cardiologos de Mexico. All rights reserved.